Systematic Literature Review: The Role Of Audit Risk On Audit Quality - Almira Yumna Putri; Enggar Diah Puspa Arum (Cita konsultindo, 2025)
This study employs a Systematic Literature Review (SLR) approach with the aim of identifying the role of audit risk on audit quality and subsequently mapping the related research findings.This research is a Systematic Literature Review (SLR) examining the role of audit risk on audit quality and compiling thematic and methodological mapping of previous studies. The results affirm that audit quality is influenced not merely by the level of risk auditors confront, but also by the institution’s capacity to integrate technological capabilities, sustain effective internal control frameworks, and uphold ethical standards across audit practices. Thus, future research should focus on developing an audit model that is more adaptive to digital advances, auditor behavior, and cross-country comparative analysis to gain a comprehensive understanding of the relationship between audit risk and audit quality in a global context. Evidence gathered from eighteen international publications confirms that audit risk significantly influences the resulting level of audit quality. The distinct contribution of this study lies in its application of the SLR method to a concentrated analysis of audit risk and audit quality, specifically across research works published between 2018 and 2025.